Pengaruh Edukasi Gizi terhadap Pengetahuan Ibu tentang Stunting di Desa Kamal Kabupaten Seram Bagian Barat - Zasendy Rehena; Monike Hukubun; Andriana Ritje Nendissa (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2020)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for children for a long time due to food intake that is not in accordance with nutritional needs which has an impact on stature height of children. Stunting in toddlers can be caused by the mother's knowledge of improper food selection. Increasing knowledge of mothers in choosing healthy foods for toddlers can be done through public health programs, one of which is by providing health education or nutrition education by means of extension which is an intervention to change knowledge and behavior as a determinant of health or public health. The purpose of this study was to determine the effect of nutrition education on maternal knowledge about stunting in Kamal Village, West Seram Regency. This type of research is a Quasi-experimental with a one group pretest - postest design. This research was conducted in February 2020 in Kamal village, West Seram Regency. Sampling was done by using the total sampling method. The T-Test results showed that the P value was 0.000 <α 0.05, which means that there was a significant difference in maternal knowledge before and after receiving counseling, namely an increase in maternal knowledge about the meaning of stunting, a factor that causes stunting. , how to prevent and overcome it in children under five. Suggestions for mothers to be more involved in health education activities. For health agencies to be able to provide regular health education for mothers.